The optimal timing of post-treatment sampling for the assessment of anthelminthic drug efficacy against Ascaris infections in humans. Issue 1 (April 2018) - Levecke, Bruno; Easton, Alice V.; Cools, Piet; Albonico, Marco; Ame, Shaali; Gilleard, John S.; Keiser, Jennifer; Montresor, Antonio; Prichard, Roger; Vlaminck, Johnny; Vercruysse, Jozef
Abstract: The egg reduction rate (ERR) is the current standard mean to assess the efficacy of drugs against human soil-transmitted helminths (STHs; Ascaris lumbricoides, Trichuris trichiura and hookworm). Although the timing of post-treatment sampling is pivotal for a readily interpretation of drug efficacy, there is lack empirical data that allows recommending the optimal time point for a follow-up egg counting. In the present study, we re-analyzed both the kinetics of worm expulsion and egg output for Ascaris lumbricoides following a single oral dose of albendazole in a series of studies previously conducted in Kenyan communities. The results indicate that it takes up to 10 days post-treatment before the expulsion of both adult male and female Ascaris worms is completed, approximately 20% of the worms being expelled between day 7 and 10 post-treatment. The sequential analysis of the egg out put, indicated a poor ERR (89.4%) at day 7 post-treatment, but a 100% ERR at day 14 and 21 post-treatment. Based on our findings we recommend to wait at least 14 days after an albendazole treatment before conducting the follow-up egg count. Any sampling before this time point may result in biased ERR estimates, due the release of residual eggs from moribund or degenerating worms.